Comparison of Two Different Proprioception Measurement Methods in the Shoulder Joint - KILIÇ, TALHA; KURU ÇOLAK, TUĞBA; ÖZGÜL, BAHAR (My University, 2024)
Aim: Proprioception assessment is important in shoulder rehabilitation. Proprioception sense can be evaluated with different methods in the clinical setting. The aim of this study was to compare shoulder proprioception measurements made with universal goniometer and isokinetic system. Methods: A total of 52 healthy individuals with a mean age of 24.6 ±4.29 years were included in the study. Shoulder proprioception was evaluated three times with a universal goniometer and isokinetic device at 30, 45 and 60 degrees shoulder flexion angles with eyes closed in a sitting position and mean values were recorded. Results: When the results obtained with the two measurement methods were compared, it was determined that there was a significant difference between the mean values (for 30, 45 and 60 degrees shoulder flexion angles, p=0.003, 0.005, 0.000, respectively) and there was no correlation relationship between the results of the two measurement methods (p<0.05). However, when the mean deviation from the target angle was compared with both measurement methods, it was determined that there was no significant difference between the measurement methods (p<0.05). Conclusion: The findings of this study demonstrated that when shoulder proprioception was measured using a goniometer or an isokinetic dynamometer at various angles, different values could be obtained. However, since the differences compared to the target angle are similar for the two measurement methods, both assessment methods can be used for proprioception evaluation. Keywords: Assessment, shoulder, proprioception, rehabilitation

Amaç: Omuz rehabilitasyonunda propriyosepsiyon değerlendirmesi önem taşımaktadır. Propriyosepsiyon duyusu klinik ortamda farklı yöntemlerle değerlendirilebilir. Bu çalışmanın amacı universal gonyometre ve izokinetik sistem ile yapılan omuz propriosepsiyon ölçümlerini karşılaştırmaktı. Gereç ve Yöntem: Çalışmaya yaş ortalaması 24,6 ± 4,29 yıl olan toplam 52 sağlıklı birey dahil edildi. Omuz propriosepsiyonu, oturur pozisyonda gözler kapalı iken 30, 45 ve 60 derece omuz fleksiyon açılarında universal gonyometre ve izokinetik cihaz ile üç kez değerlendirildi ve ortalama değerler kaydedildi. Bulgular: İki ölçüm yöntemi ile elde edilen sonuçlar karşılaştırıldığında, ortalama değerler arasında anlamlı fark olduğu (30, 45 ve 60 derece omuz fleksiyon açıları için sırasıyla p=0,003, 0,005, 0,000) ve iki ölçüm yönteminin sonuçları arasında korelasyon ilişkisi olmadığı tespit edildi (p<0,05). Ancak hedef açıdan ortalama sapma her iki ölçüm yöntemi ile karşılaştırıldığında ölçüm yöntemleri arasında anlamlı bir fark olmadığı tespit edilmiştir (p<0,005). Sonuç: Bu çalışmanın bulguları, omuz propriyosepsiyonu gonyometre veya izokinetik dinamometre kullanılarak çeşitli açılarda ölçüldüğünde farklı değerler elde edilebileceğini göstermiştir. Bununla birlikte, hedef açıya kıyasla farklılıklar iki ölçüm yöntemi için benzer olduğundan, her iki değerlendirme yöntemi de propriyosepsiyon değerlendirmesi için kullanılabilir. Anahtar Kelimeler: Değerlendirme, omuz, propriosepsiyon, rehabilitasyon
Omuz Ekleminde İki Farklı Propriyosepsiyon Ölçüm Yönteminin Karşılaştırılması
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Assessment; shoulder; proprioception; Değerlendirme; omuz; propriosepsiyon; rehabilitasyon